2013
DOI: 10.1126/science.1236188
|View full text |Cite|
|
Sign up to set email alerts
|

Nuclear PTEN Controls DNA Repair and Sensitivity to Genotoxic Stress

Abstract: Loss of function of the Phosphatase and tensin homologue deleted on chromosome 10 (PTEN) tumor suppressor gene is associated with many human cancers. In the cytoplasm, PTEN antagonizes the Phosphatidylinositol 3′ kinase (PI3K) signaling pathway. PTEN also accumulates in the nucleus, where its function remains poorly understood. We demonstrate that SUMOylation (SUMO) of PTEN controls its nuclear localization. In cells exposed to genotoxic stress, SUMO-PTEN was rapidly excluded from the nucleus dependent on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
377
4
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 363 publications
(403 citation statements)
references
References 22 publications
20
377
4
2
Order By: Relevance
“…After exposure to genotoxic stress, SUMO-PTEN was rapidly excluded from the nucleus, and this process depended on the phosphorylation of PTEN T398 by ataxia telangiectasia mutated. 20,37 Acetylation can also regulate PTEN activity. It has been reported that PTEN is acetylated on K125 and K128 by PCAF, on K163 by HDAC6, and on K402 by CBP.…”
Section: Regulation Of Pten Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…After exposure to genotoxic stress, SUMO-PTEN was rapidly excluded from the nucleus, and this process depended on the phosphorylation of PTEN T398 by ataxia telangiectasia mutated. 20,37 Acetylation can also regulate PTEN activity. It has been reported that PTEN is acetylated on K125 and K128 by PCAF, on K163 by HDAC6, and on K402 by CBP.…”
Section: Regulation Of Pten Functionsmentioning
confidence: 99%
“…There is no evidence proving that PTEN has a nuclear localization signal sequence and its nuclear localization may be regulated by different chemical modifications, such as phosphorylation, ubiquitylation and SUMOylation. 19,20 Within the nucleus, PTEN can act as a phosphatase or can bind with other proteins to participate in different nuclear processes. cAMP response element-binding protein (CREB), a cellular transcription factor, has been shown to be a nuclear substrate of PTEN in vivo and in vitro.…”
Section: Pten and Tumor Suppressionmentioning
confidence: 99%
“…Since PTEN-deficient cancer cells are hypersensitive to DNAdamaging agents, 26 we next examined the response of the reconstituted PTEN cell lines to the genotoxic agent, doxorubicin. We found that the WT PTEN cells exhibited decreased sensitivity to doxorubicin, whereas the PTEN Y336* and PTEN-HP1aKD mutants, and the empty control vector cells exhibited similar sensitivity to doxorubicin (Fig.…”
Section: C-terminal Truncated Pten Mutant Does Not Function As a Tumomentioning
confidence: 99%
“…17 This function of PTEN relates to its protein but not lipid phosphatase activity and is regulated by Ataxia telangiectasia mutated, a DNA damage-induced PIKK kinase. 16 Reporting recently in this journal, Bononi and co-workers 18 showed that a fraction of PTEN localizes to the endoplasmatic reticulum (ER) and mitochondria-associated membranes.…”
mentioning
confidence: 99%
“…11 Another recently discovered mechanism of PTEN nuclear localization involves SUMOylation-mediated PTEN nuclear retention. 16 Interestingly, SUMOylated nuclear PTEN participates in the cellular response to DNA damage, helping to explain the genomic instability of PTEN-deficient tumors and their sensitivity to poly(ADP-ribose) polymerase inhibitors. 17 This function of PTEN relates to its protein but not lipid phosphatase activity and is regulated by Ataxia telangiectasia mutated, a DNA damage-induced PIKK kinase.…”
mentioning
confidence: 99%